Organic photocatalysis for the radical couplings of boronic acid derivatives in batch and flow. Issue 44 (16th May 2018) - Lima, Fabio; Grunenberg, Lars; Rahman, Husaini B. A.; Labes, Ricardo; Sedelmeier, Joerg; Ley, Steven V.
Abstract : A convenient organo-photocataytic approach to the radical couplings of boronic acid derivatives is described and applied for APIs synthesis. Abstract : We report an acridium-based organic photocatalyst as an efficient replacement for iridium-based photocatalysts to oxidise boronic acid derivatives by a single electron process. Furthermore, we applied the developed catalytic system to the synthesis of four active pharmaceutical ingredients (APIs). A straightforward scale up approach using continuous flow photoreactors is also reported affording gram an hour throughput.